Human SLE variant NCF1-R90H promotes kidney damage and murine lupus through enhanced Tfh2 responses induced by defective efferocytosis of macrophages. Issue 2 (23rd September 2021) - Geng, Linyu; Zhao, Jian; Deng, Yun; Molano, Ivan; Xu, Xue; Xu, Lingxiao; Ruiz, Phillip; Li, Quanzhen; Feng, Xuebing; Zhang, Miaojia; Tan, Wenfeng; Kamen, Diane L; et al.
Abstract : Objectives: We previously identified a hypomorphic variant, p.Arg90His (p.R90H) of neutrophil cytosolic factor 1 ( NCF1, a regulatory subunit of phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 complex), as an putative causal variant for systemic lupus erythematosus (SLE), and established a knock-in (KI) H90 variant in the C57BL/6 background to study how this variant promotes lupus development. Methods: Wild type (WT) and KI littermates were assessed for immune profiles and lupus-like features. Disease activity and renal damage of patients with SLE were assessed by systemic lupus erythematosus disease activity index (SLEDAI) and renal items of systemic lupus international collaborating clinics (SLICC), respectively. Results: Compared with WT littermates, 5-week-old homozygous KI mice had reduced oxidative burst, splenomegaly, elevated type I interferon (IFN-I) scores, increased ratios of splenic follicular T helper 2 (Tfh2) to either T follicular regulatory (Tfr) or Tfh1 cells, increased ANA + follicular, germinal centre and plasma cells without spontaneous kidney disease up to 1 year of age. Pristane treatment exacerbated the immune dysregulation and induced IFN-I-dependent kidney disease in 36-week-old H90 KI female mice. Decreased efferocytosis of macrophages derived from KI mice and patients with homozygous H90 SLE promoted elevated ratios of Tfh2/Tfr and Tfh2/Tfh1 as well as dysregulated humoral responses due to reduced voltage-gated proton channel 1 (Hv1)-dependent acidification of phagosome pH to neutralise the decreased electrogenic effect of the H90 variant, resulting in impaired maturation and phagosome proteolysis, and increased autoantibody production and kidney damage in mice and patients with SLE of multiple ancestries. Conclusions: A lupus causal variant, NCF1-H90, reduces macrophage efferocytosis, enhances Tfh2 responses and promotes autoantibody production and kidney damage in both mice and patients with SLE.